Pengaruh Green Accounting Terhadap Economic Performance (Studi Kasus Perusahaan Sektor Pertambangan Dan Industri Kimia) (International Forum of Researchers and Lecturers, 2023)
This research is motivated by the progress of science, especially in the field of technology which is very fast, along with competition in the industrial sector which is getting tougher where companies have used sophisticated and modern equipment in carrying out their production activities. The research was conducted to examine the Effect of Green Accounting on Economic Performance. The quantitative approach method used uses data processing simple linear regression analysis. Return On Assets (ROA) is used to measure research variables. The sample companies for this research are 7 companies in the mining industry sector and the chemical industry sector which are listed on the IDX for the 2017-2021 period. The results of the study show that the Green Accounting variable has no positive effect on Economic Performance, as tested through the T-Test.